An Opto‐ and Thermal‐Rewrite PCM/CNF‐IR 780 Energy Storage Nanopaper with Mechanical Regulated Performance. Issue 25 (22nd May 2022) - Liu, Jin; Jiao, Dejin; Hoenders, Daniel; Lossada, Francisco; Yu, Wenqian; Zhu, Baolei; Walther, Andreas; Zhang, Qiuyu
Abstract: In spite of efforts to fabricate self‐assembled energy storage nanopaper with potential applications in displays, greenhouses, and sensors, few studies have investigated their multiple stimuli‐sensitivities. Here, an opto‐ and thermal‐rewrite phase change material/cellulose nanofibril (PCM/CNF) energy storage nanopaper with mechanical regulated performance is facilely fabricated, through 5 min sonication of PCMs and CNFs in an aqueous system. The combination of PCM and CNF not only guarantees the recyclability of PCM without leakage, but also offers nanopaper adaptive properties by leveraging the mobility and optical variation accompanying solid‐to‐liquid transition of PCM. Besides, trace near‐infrared (NIR) dye (IR 780) in it imparts a PCM‐embedded nanopaper photothermal effect to modulate the local transparency via time‐ and position‐controlled laser exposure, leading to a reusable opto‐writing nanopaper. Furthermore, since the synergistic effect of stick‐and‐slip function attributes from PCMs and pore structures are produced by calcium ions, the PCM/CNF energy storage nanopaper exhibits excellent mechanically regulated performance from rigid to flexible, which greatly enriches their application in energy‐efficient smart buildings and displays. Abstract : An opto‐ and thermal‐rewrite phase change material/cellulose nanofibril (PCM/CNF)‐infrared (IR) 780 energy storage nanopaper with mechanically regulated performance is facilely fabricated, through 5 min sonication of PCMs and CNFs. Trace near‐IR dye (IR 780) in it imparts a nanopaper photothermal effect to modulate the local transparency via time‐ and position‐controlled laser exposure, leading to a reusable opto‐writing nanopaper.